2020
DOI: 10.1016/j.chempr.2019.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Direct H2O2 Production in Acidic Media through Rational Design of Transition Metal Single Atom Catalyst

Abstract: The electrochemical oxygen reduction reaction in acidic media offers an attractive route for direct hydrogen peroxide (H 2 O 2 ) generation and on-site applications. Unfortunately there is still a lack of cost-effective electrocatalysts with high catalytic performance. Here, we theoretically designed and experimentally demonstrated that a cobalt single-atom catalyst (Co SAC) anchored in nitrogendoped graphene, with optimized adsorption energy of the *OOH intermediate, exhibited a high H 2 O 2 production rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
517
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(541 citation statements)
references
References 57 publications
(82 reference statements)
20
517
1
3
Order By: Relevance
“…Gao et al found that the Co SAC has the optimum close to zero ΔG OOH* among Mn, Fe, Co, Ni, and Cu, suggesting it has the highest catalytic activity toward the two-electron ORR pathway ( Figure 5C). 31 The subsequent electrochemical tests were consistent with the theoretical prediction, showing that the Co-NC SAC even slightly outperformed the best previously reported catalysts in acidic media, the Pd-Hg alloy. 114 Jiang et al conducted a study on the two-electron ORR SACs with CNTs as the support.…”
Section: Oxygen Reduction Reaction (Orr)supporting
confidence: 85%
See 1 more Smart Citation
“…Gao et al found that the Co SAC has the optimum close to zero ΔG OOH* among Mn, Fe, Co, Ni, and Cu, suggesting it has the highest catalytic activity toward the two-electron ORR pathway ( Figure 5C). 31 The subsequent electrochemical tests were consistent with the theoretical prediction, showing that the Co-NC SAC even slightly outperformed the best previously reported catalysts in acidic media, the Pd-Hg alloy. 114 Jiang et al conducted a study on the two-electron ORR SACs with CNTs as the support.…”
Section: Oxygen Reduction Reaction (Orr)supporting
confidence: 85%
“…For instance, the two-electron pathway ORR is more favorable on SACs since the adsorption of O 2 preferably takes the end-on configuration, which favors the formation of OOH* instead of O-O bond cleavage. 31 The strong metal-support interaction not only stabilizes the isolated atoms and prevents the agglomerations, but also substantially modulates the atom electronic state via charge-transfer. This is frequently discussed and demonstrated via characterization techniques and density funcitonal theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Liu and co-workers carried out a detailed kinetic analysis on Co-NC single atom catalyst for 2e − ORR in acidic media. [98] By tuning electrolyte pH and O 2 partial pressure, they observed a H + reaction order of −0.05-−0.07 and a O 2 reaction order of 0.53-0.9 within an overpotential of 0 to 250 mV, suggesting the first electron transfer step (O 2 + * + e − → *O 2 − ) to be the rate-limiting step for H 2 O 2 synthesis at this onset region (Figure 5c).…”
Section: Defects and Heteroatoms Engineering On Carbon-based Catalystsmentioning
confidence: 99%
“…Reproduced with permission. [98] Copyright 2020, Elsevier. d) Atomic distribution and coordination environmental analysis of Fe−CNT catalyst by atom probe topography, together with the determined H 2 O 2 selectivity on different motifs.…”
Section: Defects and Heteroatoms Engineering On Carbon-based Catalystsmentioning
confidence: 99%
“…97 Thirdly, the enzyme-like catalysis on SAzymes in essence is the heterocatalysis process, the selectivity arises from the differences of interaction force between single-sites and reactants, which includes the adsorption, desorption, and electron and proton transfer processes. Based on the well-established singleatom electrocatalyst and electrochemical research systems, the reaction kinetics and electrocatalytic properties of SACs could be extended to the analogous enzyme-like catalysis to ltrate highly selective SAzymes, 98 for instance, the SACs with highly selectivity in four-electron or two-electron oxygen reduction reaction electrocatalysis respectively corresponding to the halfreaction of oxidase-like or glucose oxidase-like SAzyme catalysis. 99,100 Shen et al reported the catalyst of single-atom Pt with a CuS x support (h-Pt 1 -CuS x ), which can consistently reduce O 2 to H 2 O 2 with high selectivity.…”
Section: Enzyme-like Selectivitiesmentioning
confidence: 99%